Avaliação da Fibrina Rica em Plaquetas Avançada (A-PRF) Associada à Técnica de Zucchelli no Tratamento de Recessão Gengival Tipo 1 de Cairo: Estudo Clínico Randomizado - Bin, Luiza Roberta (2022)
To evaluate the effectiveness of the Coronally Advanced Flap Modified by Zucchelli with A-PRF in root coverage in patients with gingival recession Cairo type I. Materials and Methods: The CONSORT 2010 protocol was followed for sample selection and distribution. It was a prospective study, split-mouth parallel randomized, including 54 recessions within Group RPCM+ETCS: Zucchelli Technique + ETCS; and Group 2: Zucchelli Technique + A PRF; 6 blood samples were collected; centrifugation (1300 rpm for 14 minutes, with G force of 210); and preparation of A-PRF membranes in the Stainless Steel Kit (Intra-Luck®). For the analysis of the results, the periodontal indices of height and width of the GR, probing depth, clinical insertion level, gingival level, keratinized tissue width, keratinized gingival tissue thickness, and sensitivity level, in the initial period, 90 and 180 days of following up. Statistical analysis: The GraphPad Prism 8.0 program® was used for statistical analysis. The ANOVA and TUKEY tests were performed. Kruskall-WALLIS and DUNN tests were performed to analyze the pain parameter, with a significance level of 5%. Results: The parameters probing depth and bleeding index remained without statistically significant changes in both groups. There was improvement in the parameters height and width of the recession, height of the inserted gum, thickness of the gum and level of sensitivity in both groups. There was no statistically significant difference between groups. Conclusion: There was clinical improvement in all criteria evaluated for both groups. Thus, the Coronally Advanced Flap modified by Zucchelli associated with A-PRF is as effective as the Coronally Advanced Flap modified by Zucchelli associated with ETCS.